1973
DOI: 10.1002/bs.3830180202
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and loose coupling in living systems

Abstract: Lake Forest CollegeIn line with current efforts to achieve a general view of living systems the degree of coupling is considered using specific examples at the levels of cell and organ, organism and group, organization and society. Loose coupling among systems, similar to Ashby's concept of independence, contributes to stability by allowing persistent behavior of the system in the face of certain inputs. It can be achieved either actively, by having a more tightly coupled subsystem which compensates for a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
148
0
14

Year Published

1974
1974
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(163 citation statements)
references
References 22 publications
1
148
0
14
Order By: Relevance
“…Grote (2004) summarised loose coupling through rules management to contain risks and procedural standardisation that make boundaries explicit. Glassman (1973) observed that loose coupling in nature, organisation and society contributes to stability. Whilst many suggest that loose coupling is a desirable property of system or organisational architectures, it is also variously defined and multi-faceted and influenced by strategy, technology and environmental turbulence (Orton and Weik, 1990;Beekun and Glick, 2001;Pautasso and Wilde, 2009).…”
Section: Some Observations From the Literaturementioning
confidence: 99%
“…Grote (2004) summarised loose coupling through rules management to contain risks and procedural standardisation that make boundaries explicit. Glassman (1973) observed that loose coupling in nature, organisation and society contributes to stability. Whilst many suggest that loose coupling is a desirable property of system or organisational architectures, it is also variously defined and multi-faceted and influenced by strategy, technology and environmental turbulence (Orton and Weik, 1990;Beekun and Glick, 2001;Pautasso and Wilde, 2009).…”
Section: Some Observations From the Literaturementioning
confidence: 99%
“…Some scholars suggested earlier that organizations can be "loosely coupled," both internally and externally (Aldrich, 1979;Glassman, 1973;Weick, 1979). Miller (1992 suggested that the third reason for mismatch between internal and external fit is "tunnel vision," which means that management often skip considering the environment when they are creating efficient and internally consistent 21 organizations.…”
Section: The Order Of Fitmentioning
confidence: 99%
“…Se antoja ahora caracterizarlas con el calificativo de "flojamente acopladas", aprovechando la discusión sobre el concepto que proponen Orton y Weick (1990, p. 203) y en particular la definición de Glassman (1973 apud ORTON;WEICK, 1990, p. 203): "un acoplamiento flojo se presenta cuando los sistemas tienen pocas variables en común o las variables que tienen en común son débiles." El propio Weick propone otra definición de una situación "flojamente acoplada cuando los elementos son sensibles entre sí, pero conservan evidencia de distinción e identidad propias".…”
Section: Una Relación Flojamente Acopladaunclassified